Tel Dor and Iron Age IIA Chronology - Naʾaman, Nadav (Bulletin of ASOR, 2016)
The article discusses the date and historical background of the transfer of Tel Dor from Phoenician to Israelite hands. Archaeologically, the transfer was peaceful and took place in the late Iron Age IIA. I suggest that it happened under the reign of either Omri or Ahab, at a time when Israel expanded on all fronts. Either Tel Dor was endowed as a dowry on the occasion of Jezebel's marriage to Ahab (cf. 1 Kgs 9:16), or the king of Israel purchased it as part of his alliance with Tyre (cf. 1 Kgs 9:11-14). Dating the Israelite-Tyrian alliance helps establish the date of the transition between the early and late Iron Age IIA.